Extending Fresh Chicken Eggs Shelf Life using Unconventional Methods - Abeer, M.F. Elbaz; Entsar, N. Mohamed; Entsar, S. Abdou (Food Technology Research Journal, 2024)
This study investigated the effectiveness of coating fresh chicken eggs carboxymethyl cellulose (CMC) following ozone or UV treatments on their functional properties, internal quality, eggshell breaking strength, and microbial counts during storage at 20 - 25°C for 60 days. The coatings significantly affected Haugh unit, yolk index, pH, relative whipping capacity (RWC), albumen viscosity, and total viable count (TVC) in chicken eggs. The control eggs (not treated with ozone, UV, or CMC coating) showed increasing in weight loss, pH, and yolk index, while foam stability decreased after 60 days of storage at 20 - 25°C. Microbiological results for uncoated egg samples revealed a TVC of 3.51 log10 CFU/g at the beginning of storage, reaching 8.54 log10 CFU/g by the end. In contrast, the coated eggs (both ozone + CMC and UV + CMC) reached a TVC of 6.23 log10 CFU/g. The results demonstrate the significant impact of ozone or UV treatments combined with CMC coating on chicken eggs stored at 20 - 25°C for 60 days.